PENGARUH KONDISI SOSIAL EKONOMI ORANG TUA TERHADAP PRESTASI BELAJAR DI SMKN SAJINGAN BESAR PERBATASAN - Rumia S. Tella; F. Y. Khosmas; Husni Syahrudin (Universitas Tanjungpura, 2021)
AbstractThis study aims to determine whether the socio-economic conditions of parents can affect the learning achievement of students at SMKN 1 Sajingan Besar Perbatasan. In this study, researchers used descriptive methods by using relationship studies. The data source for class X consists of 4 classes majoring in RPL 1, RPL 2, APHP, K3R. and the data is from student’s report cards and questionnaires about the socioeconomic conditions of parents. The results showed that the socio-economic conditions of parents had influence on the learning achievement of students at SMKN 1 Desa Sabunga Perbatasan, this can be seen in the regression equation Y= 63,814+4,163X and obtained t count > t table is 5,688> 2,021 then Ha is accepted and Ho is rejected. Which means that there is a positive influence of socio-economic conditions on student learning achievement, the contribution of the value of R square is 0.413 which states that the socio-economic conditions of parents have an influence on student learning achievement of 41.3%, the rest is influenced by other variables not mentioned in this study, so it is necessary further research.Keyword: Socio-Economic Conditions, Learning Achievement, SMKN 1 Sajingan